Spatiotemporal Flicker Detector Model of Motion Silencing. (December 2014) - Choi, Lark Kwon; Bovik, Alan C; Cormack, Lawrence K
Motion can impair the perception of other visual changes. Suchow and Alvarez (2011a, Current Biology, 21, 140–143) recently demonstrated a striking 'motion silencing' illusion, in which the salient changes among a group of objects' luminances (or colors, etc) appear to cease in the presence of large, coherent object motion. To understand why the visual system might be insensitive to changes in object luminances ('flicker') in the presence of object motion, we constructed similar stimuli and did a systematic spectral analysis of them. We conducted human psychophysical experiments to examine motion silencing as a function of stimulus velocity, flicker frequency, and spacing; and we created a simple filter-based model as a working hypothesis of motion silencing. From the results, we found that the threshold of silencing occurs when the log frequency of object replacement is roughly one quarter of the log flicker frequency (the mean slope is approximately 0.27). The dependence of silencing on object spacing may be explained as a phenomenon of temporal sampling of the stimuli by the visual system. Our proposed model successfully captures the psychophysical data over a wide range of velocities and flicker frequencies.